Det skotske Agerbrug ved Tangaagaard. (Fortsat.) Fra 1ste April 1861 til 1ste April 1862. - Sehested, F. (Tidsskrift for Landøkonomi, 2018)
Det skotske Agerbrug ved Tangaagaard. (Fortsat.) Fra 1ste April 1861 til 1ste April 1862.